Diare Disebabkan Infeksi Escherichia coli pada Anjing: Diarrhea Caused By Escherichia coli in Dog - Risang Aji Dewandaru; Soedarmanto Indarjulianto; Yanuartono Yanuartono; Alfarisa Nururrozi; Hary Purnamaningsih; Rusmi Hayati (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
Diarrhea is a symptom of a disease that often occurs in dogs, but the diagnosis and therapy usually only based on clinical symptoms. The purpose of this case report is to examine, diagnose and treat a dog with diarrhea. The material of this report is a 4 moths old of female mixbreed dog. The dog examinated including physical, faecal and profile blood examination. Examination of faecal samples includes gastrointestinal parasitic and bacteria identifications. The results of the anamnese and physical examination was found that the dog did not has appetite, vomited, weak, bloody diarrhea and body temperature 40.1â„ƒ. The results of faecal examinationcould be isolated Escherichia coli which was sensitive to ampicillin, and blood examination showed neutrophilia and lymphocytopenia. The dog was diagnosed suffered diahrrea caused by E. coli and was treated intra-muscularly for 5 days with 5 mg/kg body weight of ampicillin, twice a day, and 1 time 1 ml vitamin K and 0.37 ml vitamin B-complex. The results of the therapy showed a development of healing gradually and the dog was declared cured on the 7th day of treatment.